(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The lack of strong epistemological bases has led film disciplines to acquire knowledge and models from heterogeneous sources. The ‘fragility’ of the epistemological bases may be – if well managed – an opportunity for enriching and reformulate existing knowledge. For this reason, for the scientific community the issue does not concern control and regulation of forms of the discourse, identifying profiles of relevance, but its productivity: The order of the discourse about cinema will not be the order of the objects’ control, identification and perimetration, nor the order of knowledge, but it will be more properly the order of the problems that will be let arise.